O ensino da leitura na educação de jovens e adultos: o movimentum de significar e ressignificar a prática docente em contexto de pesquisa colaborativa - Santos, Adriana Cavalcanti dos (2014)
This research aimed at understanding the movimentum of signifying and resignifying the practices of reading teaching in a formation-research process in a collaborative context of continuous education, involving two teachers of the Youth and Adult Education (EJA) in two public schools, one state and another municipal, both located in the city of Maceió-AL. These schools take part in a project named Alagoas Reading Observatory in EJA (2011-2014). Accordingly, we question: which are the contributions from the theoretical-practical dialogue on the teaching of reading in adult education in the meaning and reframing process of teachers’ knowledge in the context of collaborative formation-research in the schools? In order to build this dialogue, we based on Koch (2006); Geraldi (2010a, 2010b, 2003, 1999); Hargreaves and Fullan (2001); Tardif (2002, 2005), among others. Since the study focused on a collaborative formation-research (Ibiapina, 2008), this thesis was built by means of a dialogue selfother, or rather, our-others - teachers, students and schools coordinators; professor and university students members of the above cited project - who contributed to unveil and deconstruct the singular form of the teachers’ knowledge and their ways of being a teacher and doing reading teaching in EJA. In face of the principles of this research, we experienced some steps: collaborative observations, reflective sessions on the teachers’ practices and theoretical study sessions, so that we could, from the practical knowledge of the teachers, discuss and problematize all these elements. The results indicate that the school teachers, from the knowledge that constitute the epistemology of their practices in dialogue with the theoretical and practical studies carried out, really tried to signify and signify their singular practices of teaching reading in the context in which textual genres were transformed into objects of study, in an interactive dimension between university and school; another knowledge was generated, in order to understand the complex nature of a process of collaborative formation-research. We hope that this research can contribute to (re)consider the practices of reading teaching mediated by a conception of language which, in its turn, defines the places of the school teachers and the place of the text; the didactic treatment and the place of the student in the practice of reading teaching.